Inter-relationships between the economic and emotional consequences of colorectal cancer for patients and their families: a qualitative study - Ó Céilleachair Alan; Costello Liza; Finn Claire; Timmons Aileen; Fitzpatrick Patricia; Kapur Kanika; Staines Anthony; Sharp Linda (BMC Gastroenterology, 2012)
Abstract Background While the evidence-base concerning the economic impact of cancer for patients and their families/carers has grown in recent years, there is little known about how emotional responses to cancer influence this economic impact. We investigated the economic costs of cancer in the context of patients’ emotions and how these both shaped the patient and family burden. Methods Health professionals from six hospitals invited patients diagnosed with colorectal cancer (ICD10 C18-C20) within the previous year to take part in the study. Semi-structured face-to-face interviews were conducted with patients and, where available, a family member. Interviews covered medical and non-medical costs incurred as a result of cancer and the impact of these on the lives of the patient and their family. Interviews were audio-recorded. Recordings were transcribed verbatim and these data were analysed qualitatively using thematic content analysis. Results Twenty-two patients with colorectal cancer (17 colon and 5 rectal; 14 women and 8 men) were interviewed; 6 were accompanied by a family member. Important cancer-related financial outlays included: travel and parking associated with hospital appointments; costs of procedures; increased household bills; and new clothing. Cancer impacted on employed individuals’ ability to work and depressed their income. The opportunity cost of informal care for carers/family members, especially immediately post-diagnosis, was a strong theme. All patients spoke of the emotional burden of colorectal cancer and described how this burden could lead to further costs for themselves and their families by limiting work and hindering their ability to efficiently manage their expenses. Some patients also spoke of how economic and emotional burdens could interact with each other. Support from employers, family/carers and the state/health services and patients’ own attitudes influenced this inter-relationship. Conclusions The economic impact of colorectal cancer on patients and their families is complex. This study suggests that the economic costs and the emotional impact of cancer are often related and can exacerbate each other, but that various factors can meditate this inter-relationship.